Factors Associated with Survival Rate after Cardiopulmonary Resuscitation - Sanaz Amini; Mohammad Taghi Moghadamnia; Ezzat Paryad; Ehsan Kazem Nezhad Leyli (Guilan University of Medical Sciences, 2017)
Introduction: Cardiovascular disease is considered as the most important cause of mortality among men and women throughout the world. This condition causes sudden cardiac arrest in more than half of the cases. To reduce mortality due to this disease, cardiopulmonary resuscitation (CPR) and the determinants of its success are the focus of researchers. Objective: The aim of this study was to determine the survival rate of CPR and its associated factors in patients with in-hospital cardiac arrest in a teaching medical center in Rasht. Materials and Methods: The present descriptive-analytic cross-sectional study investigated 100 patients undergoing CPR during spring-summer 2014 at Specialized Cardiology Center in Rasht. The instrument of this study was the standard checklist of Utstein-Style that included information on age, gender, cause of cardiac arrest, rhythm, work shift, CPR place, interval of cardiac arrest until arrival of CPR team, interval of cardiac arrest until shock, interval of cardiac arrest until intubation, interval of cardiac arrest until CPR termination, short-term and long-term outcomes of CPR, and brain function status until discharge from the hospital. Data was analyzed using descriptive statistics (mean, standard deviation) and analytic analyses (T-test, Fisher s exact test, analysis of variance, and logistic regression). Results: A total of 53% of subjects were male and mean age of the patients was 68.6 ± 14.4 years; 30% of patients who underwent CPR had short-term survival, and 11% were discharged with appropriate brain status with Glasgow Coma Scale (GCS=15). Multiple logistic regression (Backward LR method) revealed that only gender (p=0.008, OR=6.46, CI95%: 1.63-25.5) and electric shock (p=0.03, OR=4.1, CI95%: 1.1-15.14) were statistically significant predictors of short-term survival. Conclusion: According to the results of this study, time is an important factor in CPR outcome and increasing the survival rate and timely use of electric shock can be an effective measure in shockable rhythms. Appropriate planning, training staff, and using appropriate facilities, as well as establishment of a primary warning system for calling CPR team in health centers can increase the success rate of CPR.